Escola e fábrica: discursos sob tensão - Franco, Márcia Garbini (2008)
This dissertation has for objective to investigate the verbal-visual construction of the work notion found in research reports developed by apprentices of a vocational school, located inside of the company who supports the school. The reports are resulted of the project "Ergonomics in the workstations" that, supported theoretically in the British analysis ergonomic of workstations, has as goal the development of activities of compensation postural and physical preparation for the work. The corpus is constituted by 11 reports selected in the period between 2004 and 2006 that, besides the text, presents pictures, in way to suggest the verbal-visual analysis. The theoretical perspective that bases this dissertation is centered in Bakhtin and its Circle and more directly in concrete statement, mentioned speech, controversial speech and spheres of communication. Besides this basis and to take the images and their implications in the construction of the work notion, I looked for support in Susan Sontag's studies about photography, mainly in what she refers to the subject of the photographic vision, and of Ivan Lima regarding the relationship of visual dominance. Starting from the identification of some verbal and visual elements which compose the materiality of the text, as well as in the ways of presence of the other in the speech and of the social voices which compose the corpus, it was possible to establish relationships between the verbal and the look that participate indeed of the construction of the work notion in the reports. The results of the analysis indicated the "contradiction" as element who structures of the corpus. The images revealed a subject behind the camera, in other words, the subjectivity and, articulate to the verbal elements, appear a confrontation among the voices that permeate the corpus: the Ergonomics, speech worked by the school, is revealed as the place of the ideal; the practices in the workstations of the company, are exposed as space of the Real; the speech of the technology and quality and the one of the survival as aspects that surround the work. Finally, the presence of the suitable speeches for the analysis of the corpus, put in confrontation situation, signals the contradictions that permeate the work notion, as demonstrated by the reports